2013
DOI: 10.1038/aps.2013.96
|View full text |Cite
|
Sign up to set email alerts
|

Sodium hydrosulfide alleviates lung inflammation and cell apoptosis following resuscitated hemorrhagic shock in rats

Abstract: Aim: To investigate the protective effects of hydrogen sulfide (H 2 S) against inflammation, oxidative stress and apoptosis in a rat model of resuscitated hemorrhagic shock. Methods: Hemorrhagic shock was induced in adult male SD rats by drawing blood from the femoral artery for 10 min. The mean arterial pressure was maintained at 35-40 mmHg for 1.5 h. After resuscitation the animals were observed for 200 min, and then killed. The lungs were harvested and bronchoalveolar lavage fluid was prepared. The levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 47 publications
3
19
0
2
Order By: Relevance
“…Coagulopathies in microcirculation, lipase and phospholipase activities; and arteriovenous shunts opened by the release of kinines are the triggering factors leading to the development of ARDS (33). In the present study, LDH in BAL fluid and MDH Xu et al (14) Showed that H 2 S prevents lung injury, inhibits apoptosis and decreases inflammatory response in hemorrhagic shock-induced rats. Also, in a study by Lıu et al (39) it was reported that H 2 S inhibits Fas pathway and has preventive effectsin acute lung injury-induced rats.…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…Coagulopathies in microcirculation, lipase and phospholipase activities; and arteriovenous shunts opened by the release of kinines are the triggering factors leading to the development of ARDS (33). In the present study, LDH in BAL fluid and MDH Xu et al (14) Showed that H 2 S prevents lung injury, inhibits apoptosis and decreases inflammatory response in hemorrhagic shock-induced rats. Also, in a study by Lıu et al (39) it was reported that H 2 S inhibits Fas pathway and has preventive effectsin acute lung injury-induced rats.…”
Section: Discussionsupporting
confidence: 53%
“…NaHS addition did not show any decrease in IL-6 levels. However, Xu et al (14) showed that H 2 S inhibits TNF-α and IL-6 in their study.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations